Survival outcomes in surgically treated patients with advanced laryngeal cancer in Serbia - Milovanović, Jovica; Jotić, Ana; Tešić Vidović, Ljiljana; Djukić, Vojko; Trivić, Aleksandar; Krejović Trivić, Sanja; Radin, Zorana; Savić Vujović, Katarina; Milovanović, Andjela; Banko, Bojan; Artiko, Vera (Vojnosanitetski pregled, 2021)
Abstract Background/Aim. Laryngeal carcinomas make 1%–3% of all head and neck malignancies.Treatment outcome and survival rates depend greatly on established stage of the disease. The purpose of this study was to examine the survival of the patients with advanced laryngeal carcinoma depending on gender, age, common risk factors (tobacco and alcohol use), primary tumor localization, histopathological tumor grade, clinical TNM (tumor, node and metastasis) stage and surgical treatment of the disease. Methods. Retrospective study included 252 patients treated surgically for advanced squamocellular carcinoma of the larynx in a three-year period with five-year follow-up. Patients included in the study were treated primary with surgery, with postoperative radiotherapy and chemotherapy depending on the stage of the disease, intraoperative findings and tumor resection borders. Overall survival and disease-specific five-year survival of patients was calculated for demographical and clinical characteristics of the patients. Results. Overall 5-year survival of patients with operable advanced laryngeal cancer included in the study was 86.14% and disease-specific survival 86.51%. Lower overall and the disease-specific survival was associated with age, higher histological tumor grade and more extensive neck dissections. Conclusion. Primary total laryngectomy results in higher survival outcomes in cases of transglottic T3 and T4a laryngeal tumors. Patients should be informed of the likely increased mortality risks tied to the choice of surgical resection and treatment modality before their decision.